Al-doped ZnO: Electronic, electrical and structural properties - Maldonado, F. (2010)
Changes in structural, electrical and electronic properties of zinc oxide (ZnO) due to Al doping are studied using a quantum-chemical approach based on the Hartree-Fock theory. A periodic supercell of 128 atoms has been exploited throughout the study. The atomic parameters for Zn atom were obtained by reproducing the main properties of ZnO crystal as well as the first three ionization potentials of Zn atom. The perturbation imposed by Al atom incorporation leads to the atomic relaxation, which is computed and discussed in detail. A novel effect of electron density redistribution between different atomic orbitals within the same atom has been found. This phenomenon influences atomic rearrangement near Al impurity. The Al doping generates a free electron in the conduction band, which can be considered as a large radius electron polaron increasing the n-type electrical conductivity in the crystal in agreement with the known experimental data. The obtained small increase in the band-gap width due to the impurity incorporation resolves existing experimental debates on this point. © 2010 Elsevier Ltd. All rights reserved.